2020
DOI: 10.7759/cureus.10889
|View full text |Cite
|
Sign up to set email alerts
|

Waardenburg Syndrome Type-II in Twin Siblings: An Unusual Audio-Pigmentary Disorder

Abstract: Waardenburg syndrome (WS) is an interesting inherited audio-pigmentary disorder. The syndrome shows no gender, racial, or ethnic predilection. This unique disorder is characterized by pigmentary abnormalities, deafness, and neural crest-derived tissue defect. WS can be recognized by some specific clinical features that appear after birth; not all affected individuals possess all the clinical features. It has four clinical sub types based on the mutant gene and characteristic morphology. These morphological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Pathogenic variants in the SOX10 gene provide an outstanding example for studying genetic variation and phenotypic pleiotropy. Mutations in this gene can lead to the clinical manifestations of either the WS2 or the WS4 phenotype [Masood et al, 2020]. The SOX10 gene encodes the protein SOX10 (SRY [sex determining region Y] box 10), a transcription factor that regulates the neural crest [Chaoui et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic variants in the SOX10 gene provide an outstanding example for studying genetic variation and phenotypic pleiotropy. Mutations in this gene can lead to the clinical manifestations of either the WS2 or the WS4 phenotype [Masood et al, 2020]. The SOX10 gene encodes the protein SOX10 (SRY [sex determining region Y] box 10), a transcription factor that regulates the neural crest [Chaoui et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…A rare case of infant male twins was presented by medical researchers from Karachi and Quetta, in Pakistan (Masood et al, 2020). The twins met the criteria for one of the four subtypes (WS-II) of Waardenburg's syndrome, that is, white forelock, heterochromia (different colored irises), hearing loss and affected first degree relative(s).…”
Section: Recent Twin Casementioning
confidence: 99%
“…The researchers noted that for a child to be affected only one parent had to transmit the relevant gene; this mode of transmission suggests dominant inheritance, except that neither parent was affected. As Masood et al (2020) indicated, different types of gene mutations, such as insertions and deletions, may explain this syndrome. Furthermore, a recessive form of the condition (WS-II) is recognized, as I explain below.…”
Section: Recent Twin Casementioning
confidence: 99%